Tracing the Academic Legacy of Prof. Dipankar Das Sarma, Renowned Scientist from IISc Bengaluru: A Bio-Bibliometric Analysis of Scientific Productivity and Research Impact - Madhu, S (Information Research Communications, 2026)
Objectives This study presents a bio-bibliometric analysis of the research productivity, citation impact, and collaborative patterns of Dipankar Das Sarma over the period 1980-2025. Methodology The present study utilised Scopus, a widely recognised abstracting and citation database developed by Elsevier, for the retrieval of bibliographic records through author-based search strategy. The extracted data were subsequently curated, organised, and tabulated using Microsoft Excel for descriptive and statistical analysis. In addition, VOSviewer was employed to generate collaboration networks and thematic visualisation maps, enabling the identification of research linkages and thematic structures within the scholarly output of the author. Results The findings indicate a steady increase in output, with 2004-2015 emerging as the most productive phase (177 publications; 34.30%), while 1992-2003 showed the highest citation intensity (CPP: 58.82). Research articles dominated the output (85.85%), though review papers demonstrated higher citation impact. The analysis further reveals a strong collaborative pattern, with 507 multi-authored publications (98.26%) and a collaboration coefficient of 0.98, including 272 international collaborative papers (52.71%) generating 11,234 citations. The global collaboration network spans 38 countries, with major partnerships involving Germany, Italy, Japan, and the United States. Keyword analysis identified 2,314 terms, with dominant themes such as perovskite, electronic structure, and nanocrystals, alongside high linkage strength in nanoscience-related topics. Conclusion Overall, the findings highlight sustained productivity, significant citation impact, and extensive collaboration as key factors underpinning the author’s scholarly influence.
Keywords: Bio-Bibliometrics; Collaboration Co-efficient; IISc; India; Publication Productivity; Scientometric Portrait.